Red Lionfish (Pterois volitans) Invade San Salvador, Bahamas: No Early Effects on Coral and Fish Communities - Alexander, Amanda K; Haynes, James M (International Journal of Bahamian Studies, 2011)
Biological invaders are a leading contributor to global losses of biodiversity. A recent invader to the waters surrounding San Salvador, Bahamas, the red lionfish, Pterois volitans, was first reported in 2006; by 2009 they were common in waters 2-40 m deep around the island. Our study collected data on coral communities and fish assemblages at three patch reef complexes (Rice Bay, Rocky Point, Lindsay Reef) in 2007, during the initial phase of the invasion, and compared the results to a nearly identical study done in 2001 before P. volitans colonized San Salvador. Prey selection and quantity of consumption by P. volitans were also examined. Coral and fish species richness, diversity, percent cover (corals) and abundance (fish) were similar in 2001 and 2007. Of the 5,078 fish recorded during our study on shallow patch reefs, only two were P. volitans, but they were more prevalent in deeper water along San Salvador’s “wall.” Captured P. volitans ranged in size from 19-32 cm, all longer than maturity length. Pallid goby (Coryphopterus eidolon), black cap basslet (Gramma melacara) and red night shrimp (Rynchocienetes rigens) were the most commonly identified stomach contents. The effects of the successful invasion and increasing population of P. volitans on San Salvador’s reef ecosystem are uncertain at this time; future monitoring of potential changes in coral and fish communities on the patch reefs of San Salvador is recommended to determine if population control measures need to be considered. Initial post-invasion data (2007), along with pre-invasion data (2001), are valuable benchmarks for future studies.